In vivo platelet activation and platelet hyperreactivity in abacavir-treated HIV-infected patients - Falcinelli, Emanuela; Francisci, Daniela; Belfiori, Barbara; Petito, Eleonora; Guglielmini, Giuseppe; Malincarne, Lisa; Mezzasoma, AnnaMaria; Sebastiano, Manuela; Conti, Valentina; Giannini, Silvia; Bonora, Stefano; Baldelli, Franco; Gresele, Paolo (Thrombosis and Haemostasis, 2013)
Abacavir (ABC) has been associated with ischaemic cardiovascular events in HIV-infected patients, but the pathogenic mechanisms are unknown. Aim of our study was to assess whether ABC induces in vivo platelet activation and ex vivo platelet hyper-reactivity. In a retrospective, case-control study, in vivo platelet activation markers were measured in 69 HIV-infected patients, before starting therapy and after 6–12 months of either ABC (n=35) or tenofovir (TDF) (n=34), and compared with those from 20 untreated HIV-infected patients. A subgroup of patients was restudied after 28–34 months for ex vivo platelet reactivity. In vivo platelet activation markers were assessed by ELISA or flow cytometry, ex vivo platelet reactivity by light transmission aggregometry (LTA) and PFA-100®. The in vitro effects of the ABC metabolite, carbovir triphosphate, on aggregation and intra-platelet cGMP were also studied. sPLA2, sPsel and sGPV increased significantly 6–12 months after the beginning of ABC, but not of TDF or of no treatment. Ex vivo platelet function studies showed enhanced LTA, shorter PFA-100® C/ADP closure time and enhanced platelet expression of P-sel and CD40L in the ABC group. The intake of ABC blunted the increase of intraplatelet cGMP induced by nitric oxide (NO) and acutely enhanced collagen-induced aggregation. Preincubation of control platelets with carbovir triphosphate in vitro enhanced platelet aggregation and blunted NO-induced cGMP elevation. In conclusion, treatment with ABC enhances in vivo platelet activation and induces platelet hyperreactivity by blunting the inhibitory effects of NO on platelets. These effects may lead to an increase of ischaemic cardiovascular events.
Keywords: Abacavir; cardiovascular risk; guanylyl cyclase; nitric oxide; platelet aggregation